Risk factor analysis of childhood and adolescent thyroid cancer mediastinal lymph node and distant metastasis - Zhang, Ruirui; Sun, Mengjin; Ding, Siyue; Niu, Jinling; Wang, Shuhui; Li, Qian (Frontiers in Oncology, 2025)
ObjectiveThe aim of this study is to explore the risk factors related to mediastinal lymph node metastasis (MLNM) and distant metastasis (DM) in children and adolescents with thyroid cancer.MethodThis is a retrospective analysis of children and adolescent thyroid cancer patients admitted to our hospital from January 2015 to October 2022. The clinical and pathological data, and the preoperative ultrasound features of the patients were statistically analyzed.ResultsThis study included a total of 67 patients, consisting of 20 males and 47 females. Among them, 14 cases (20.9%) had mediastinal lymph node metastasis and 21 cases (31.3%) had distant metastasis. The univariate analysis showed that gender, the central metastatic lymph node ratio (CCLNR), and DM were all correlated in MLNM. The nodule morphology, location, the CCLNR, and MLNM were identified as related factors in DM. The multivariate regression results showed that gender and DM were independent MLNM risk factors. Furthermore, the lesion morphology and the CCLNR were identified as independent DM risk factors.ConclusionThe larger the CCLNR ratio, the higher the likelihood of the development MLNM and DM in children and adolescent thyroid cancer patients. A CCLNR > 0.79 as an evaluation index can indicate that children and adolescents with thyroid cancer are at higher risk of developing MLNM and DM.